Methods for assessing phosphorus overfeeding on organic and conventional dairy farms. (27th November 2013) - Nordqvist, M.; Holtenius, K.; Spörndly, R.
<x content-type="archive" xml:space="preserve">Abstract</x> Phosphorus (P) losses from dairy farms can severely damage aquatic ecosystems, so it is important to have tools to assess overfeeding of P. This study screened P intake and faecal excretion of different P fractions in dairy cows on conventional and organic farms, compared the P feeding level of the herds against the recommendations and analysed different sampling and analysis methods for assessing the general status of P feeding on the farms. The organic (n=14) and conventional farms (n=15) were of comparable size and were located in southern Sweden. On each farm, feed intake was registered for 10 cows representing four different lactation stages and their P intake was calculated and related to current recommendations. Faecal samples taken from the same cows were analysed for total P (TP) and soluble P. Milk production data for the cows were obtained from the Swedish official milk recording scheme. TP was determined in one slurry sample per farm. More than 70% of the cows studied, representing both conventional and organic herds, consumed P in excess of the recommendations. Conventional herds had higher P content in the ration than organic herds, and lactating cows in conventional herds had higher faecal concentrations of total and soluble P than those in organic herds. However in dry cows, the P content of the ration and soluble P and TP in faeces did not differ between the two management systems. Soluble P was well correlated to TP in faeces, and both were good indicators of P overfeeding.